A novel MAPT variant (E342K) as a cause of familial progressive supranuclear palsy - Li, Hang; Li, Qijun; Weng, Qin; Cui, Ruixue; Yen, Tzu-Chen; Li, Yanfeng (Frontiers in Neurology, 2024)
Background MAPT variants are a known cause of frontotemporal dementia and Parkinsonian syndrome, of which progressive supranuclear palsy syndrome (PSP) is a rare manifestation. Objective To report a novel MAPT variant in a PSP pedigree with autosomal dominant inheritance pattern, and to produce a literature review of PSP patients with MAPT variants. Methods A comprehensive clinical, genetic, and molecular neuroimaging investigation was conducted on a 61 years-old female proband diagnosed with PSP. We also collected the clinical presentation data and history of the patient’s pedigree, and performed further genetic analysis of 4 relatives, from two generations, with and without symptoms. Results The proband exhibited typical clinical manifestation of PSP. A cranial MRI revealed midbrain atrophy, and an FDG-PET scan suggested hypo-metabolic changes in caudate nucleus, left prefrontal lobe, both temporal poles, and midbrain. 18F-florzolo-tau-PET revealed tau-protein deposits in the thalamus and brainstem bilaterally. A gene test by whole-exome sequencing identified a novel MAPT variant [NM_005910.6, exon 11, c.1024G > A (p.E342K)], and the same variant was also identified in one affected relative and one asymptomatic relative, a probable pre-symptomatic carrier. Conclusion The PSP pedigree caused by the novel MAPT (E342K) variant, expanded the mutational spectrum of MAPT.